2005
DOI: 10.1007/s10735-004-2912-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and endothelin receptors in the basilar artery of the capybara

Abstract: Little is known about cerebral vasculature of capybara, which seems may serve as a natural model of studying changes in cerebral circulation due to internal carotid artery atrophy at animal sexual maturation. This is the first study of the light- and electron-immunocytochemical localisation of endothelin-1 (ET-1) and ETA and ETB endothelin receptors in the basilar artery of capybaras (6 to 12-month-old females and males) using an ExtrAvidin detection method. All animals examined showed similar patterns of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…According to the present study, the reverse is true in RPMVEC where the effects of microinjected ET-1 are mediated through intracellular ET B receptors. Our findings are particularly relevant considering the ability of endothelial cells to synthesize ET-1 (40 -42) and make it available within the cytoplasm (32,33,40) to activate its intracellular targets. Importantly, a majority of the responses elicited by ET-1 in the endothelium, including the release of vasorelaxant factors such as NO, prostacyclin, and endothelium-derived hyperpolarizing factor are ET B receptor-dependent (11).…”
Section: Discussionmentioning
confidence: 89%
“…According to the present study, the reverse is true in RPMVEC where the effects of microinjected ET-1 are mediated through intracellular ET B receptors. Our findings are particularly relevant considering the ability of endothelial cells to synthesize ET-1 (40 -42) and make it available within the cytoplasm (32,33,40) to activate its intracellular targets. Importantly, a majority of the responses elicited by ET-1 in the endothelium, including the release of vasorelaxant factors such as NO, prostacyclin, and endothelium-derived hyperpolarizing factor are ET B receptor-dependent (11).…”
Section: Discussionmentioning
confidence: 89%
“…Immunohistochemical analysis of the capybara basilar artery provided evidence of adventitial ET B receptors (24). However, results from an earlier study (19) suggested that ET B receptors were not present in the adventitia derived from a tissue-engineered human blood vessel.…”
Section: Discussionmentioning
confidence: 91%
“…Cross-sections of the BA ( ∼ 100 μm thick) were cut using a vibratome (Technical Product International, Inc., St. Louis, Mo., USA), collected in PBS and processed for EM-I of ET-1, ET A and SYP [Loesch et al, 2005;Steele et al, 2006;Loesch et al, 2010a]. Briefly, sections were exposed to 0.3% hydrogen peroxide in 33% methanol for 45 min (in order to block endogenous peroxidases), washed in PBS and then for ET-1 detection placed for 1 h in a 10% nonimmune normal goat serum (NGS; Nordic Immunology, Tilburg, The Netherlands), while for the detection of ET A and SYP sections were placed in a 10% nonimmune normal horse serum (NHS; Jackson ImmunoResearch Laboratories, West-Grave, Pa., USA).…”
Section: Em-i Of Et-1 Et a And Sypmentioning
confidence: 99%
“…Less is known regarding the presence and role of ET-1 and its receptors in cerebrovascular nerves [Loesch et al, 1998[Loesch et al, , 2005. So far, the presence of ET-1-positive cerebrovascular autonomic nerves has been reported in the BA of the rat [Loesch et al, 1998;Milner et al, 2000] and of the human middle cerebral artery [Loesch and Burnstock, 2002;Mickey et al, 2002].…”
mentioning
confidence: 99%
See 1 more Smart Citation